Deadly Cities? A Note on Spatial Inequalities in Mortality in Sub-Saharan Africa - Isabel Günther; Kenneth Harttgen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
In this paper we analyze if an `urban mortality penaltyéxists for todayś developing countries, repeating the history of industrialized nations during the 19th century. We analyze the Demographic and Health Survey (DHS) of 19 Sub-Saharan African countries for differences in child and adult mortality between rural and urban areas. Our findings indicate that child mortality is higher in rural areas for almost all countries. On average child mortality rates are 13.6 percent in rural areas and `only\' 10.8 percent in urban areas. In contrast, average urban adult mortality rates (on average 14.5 percent) have indeed exceeded rural adult mortality rates (on average 12.8 percent) in many of our sample countries in the 2000s. For many countries high child mortality pockets do, however, exist in slum areas within cities. Child mortality rates in slum areas are on average 1.65 times higher than in the formal settlements of cities, but still lower than in rural areas.
Keywords: I10; I30; J10; R00; 330; mortality; urban; slum; inequality